Using Google Trends and Twitter for Prostate Cancer Awareness: A Comparative Analysis of Prostate Cancer Awareness Month and Breast Cancer Awareness Month - Johnson, Bradley S (Cureus, 2021)
Background We evaluated (1) whether the public interest in prostate cancer and prostate cancer screening increased following Prostate Cancer Awareness Month (PCAM) and (2) whether PCAM was as effective as Breast Cancer Awareness Month (BCAM) at generating public interest. Methods  Using Google Trends, we measured search volume in PCAM and BCAM. We used the search volume in Google Trends as a proxy for changes in public interest from January 01, 2009 to December 31, 2018 worldwide, including the specific keywords: “Prostate Cancer”; “Prostate-Specific Antigen”; “Prostate Cancer Screening”; “Prostate Cancer Management”; “Breast Cancer”; “Breast Cancer Screening”; “Mammography”; and “Breast Cancer Management”. Also, we measured tweets containing “prostate cancer” and “breast cancer”. We used an autoregressive integrated moving algorithm (ARIMA) to forecast expected weekly search volumes during PCAM and BCAM. We then compared the Google Trends data from during PCAM and BCAM to the forecasted values and determined a “greater than expected” range. Results The mean pooled percent increase in tweets associated with “prostate cancer” during PCAM from 2012 through 2018 was 15.9% (95% CI, -1% - 33%). The mean pooled percent increase in tweets associated with “breast cancer” during BCAM from 2012 through 2018 was 318.5% (95% CI, 268% - 369%). BCAM was associated with a 302.6% greater effect on increasing tweets referencing the disease of interest than PCAM from 2012-2018. “Breast cancer” Google searches were found to be 36.7% (95% CI, 34% - 39%) more frequent than “prostate cancer” per month from 2009-2019. Google Searches for “breast cancer screening” were 29.6% (95% CI, 28% - 31%) greater than “prostate cancer screening”. Conclusions Our results indicate that PCAM is not generating substantial internet interest, especially when compared to BCAM. The search volume for Google Trends search terms related to PCAM was less than BCAM in every comparison, and Twitter indicated only a slight increase of Tweets during the month of PCAM. Suggestions are provided to improve the effect of PCAM and men’s health.